2000
DOI: 10.1177/000331970005100601
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a 4-Week Treatment with Prostaglandin E1 on Health-Related Quality of Life of Patients with Intermittent Claudication

Abstract: Intermittent claudication impairs functional status and quality of life in many patients by limiting walking capacity. The aim of this study was to evaluate the effects of a 4-week treatment with prostaglandin E1 (PGE1), a drug inducing vasodilation and inhibiting platelet aggregation, on improving functional status and health-related quality of life in patients with disabling intermittent claudication. Forty-two untrained outpatients (37 men and five women, mean age 64 +/- 8 years) with intermittent claudicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Vasodilator prostaglandins are considered investigational for this indication, and none have been approved by the FDA for use in patients with PAD. Intravenous administration of PGE-1 and a PGE-1 prodrug once or twice daily for 4 to 8 weeks has been reported to increase pain-free and maximal walking distance in placebo-controlled trials (384)(385)(386)(387). Daily intravenous administrawalking distance by 40% to 60% compared with placebo after 12 to 24 weeks of therapy (161,337,338,369,370).…”
Section: Medical and Pharmacologicalmentioning
confidence: 99%
“…Vasodilator prostaglandins are considered investigational for this indication, and none have been approved by the FDA for use in patients with PAD. Intravenous administration of PGE-1 and a PGE-1 prodrug once or twice daily for 4 to 8 weeks has been reported to increase pain-free and maximal walking distance in placebo-controlled trials (384)(385)(386)(387). Daily intravenous administrawalking distance by 40% to 60% compared with placebo after 12 to 24 weeks of therapy (161,337,338,369,370).…”
Section: Medical and Pharmacologicalmentioning
confidence: 99%
“…Studies in patients with intermittent claudication demonstrated promising increases in walking distance and quality of life with alprostadil, a synthetic form of prostanoid prostaglandin E 1 (PGE 1 ), vs. control treatment [1][2][3][4]. The aim of the present prospective, randomised, active-controlled, multicentre, double-blind study (NCT01263925) was to determine, if alprostadil is superior to pentoxifylline, a common treatment for intermittent claudication at the time of the inception of the study.…”
Section: Letter To the Editormentioning
confidence: 98%
“…Translated versions of the SF-36 were used in Serbian [28], Dutch [16], French [36], Italian [29] and Chinese [39]. Of the 23 studies 5 utilised the RAND-36 tool [1, 4, 5, 30, 33], which contains the same question set as the SF-36 but is analysed differently [18]. The second most common questionnaire used was the Walking Impairment Questionnaire (WIQ) used in 8 out of 31 studies (total 749 patients) [1214, 19, 30, 33, 38, 42], including a direct comparison by Nicolai et al.…”
Section: Number Of Questionnaires Usedmentioning
confidence: 99%